2017
DOI: 10.1016/j.joca.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear optical microscopy as a novel quantitative and label-free imaging modality to improve the assessment of tissue-engineered cartilage

Abstract: SHG represents a reliable quantitative approach to assess collagen deposition in laboratory engineered cartilage, and may be applied to improve currently established scoring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Macroscopically-normal-looking cartilage, corresponding to cartilage areas looking intact to the eye and presenting no signs of abnormalities, such as tears, scratches, rugose or eroded tissue, was collected from femoral condyles during total knee replacements and was used to isolate human chondrocytes. All cell types were isolated using a mixed enzymatic-explant method, as previously described (Islam et al, 2016;Islam et al, 2017). Briefly, all tissue specimens were washed three times with sterile Dulbecco's phosphate buffered saline (PBS; D8537, Sigma-Aldrich) and minced into small pieces for subsequent enzymatic digestion in collagenase XI solution (≥ 800 units/mg solid; C9407, Sigma-Aldrich) at a final concentration of 1.25 mg/mL at 37 °C on a shaker at 400 rpm.…”
Section: Isolation and Culture Of Human Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopically-normal-looking cartilage, corresponding to cartilage areas looking intact to the eye and presenting no signs of abnormalities, such as tears, scratches, rugose or eroded tissue, was collected from femoral condyles during total knee replacements and was used to isolate human chondrocytes. All cell types were isolated using a mixed enzymatic-explant method, as previously described (Islam et al, 2016;Islam et al, 2017). Briefly, all tissue specimens were washed three times with sterile Dulbecco's phosphate buffered saline (PBS; D8537, Sigma-Aldrich) and minced into small pieces for subsequent enzymatic digestion in collagenase XI solution (≥ 800 units/mg solid; C9407, Sigma-Aldrich) at a final concentration of 1.25 mg/mL at 37 °C on a shaker at 400 rpm.…”
Section: Isolation and Culture Of Human Stromal Cellsmentioning
confidence: 99%
“…Liechty et al (2000) propose that MSCs promote tissue regeneration by engraftment of cells in damaged areas and transdifferentiation into tissue-forming cells to promote repair. Recently, paracrine signalling and release of potent bioactive factors have emerged as modulators of the microenvironment during tissue healing (Gnecchi et al, 2016;Iso et al, 2007;Prockop, 2009). In the field of cartilage repair and OA, the fate of implanted cells during biological repair procedures and their contribution to rebuilding the damaged tissue is mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of SHM for the assessment of articular cartilage in animals [11,28,30,56], humans [12,33], and tissue-engineered [44,48,57,58] cartilage constructs have been demonstrated several times. SHM can provide a wealth of information at several levels, including, but not limited to, micron-level surface morphology, changes in collagen architecture, detection of collagen types in regenerated cartilage, label-free analysis, and 3D imaging capability (optical biopsy) within the limit of laser penetration depth.…”
Section: Discussionmentioning
confidence: 99%
“…An initial effort has been undertaken by Hayley et al, which demonstrated that cartilage damage is associated with collagen redistribution, and collagen disorganization could be assigned an independent score [10]. A similar effort associated with SHM scoring system for the assessment of tissue-engineered cartilage has been also reported by Islam et al [48].…”
Section: Challenges To Shm For Cartilage Assessmentmentioning
confidence: 95%
“…Sections were imaged by bright field light microscopy (Leica DMI6000B). To quantify the in vitro chondrogenic potential, a visual semi-quantitative scoring of tissue sections (Bern score) was applied independently by three different observers [26]. The chondrogenic potential was classified into two groups according to histological outcomes: “Group A” with high chondrogenic potential (Bern score 6–9) and “Group B” with low chondrogenic potential (Bern score < 6) (Table 1).…”
Section: Methodsmentioning
confidence: 99%